Tin Hội Nghị: Đại hội Hội Địa chất Thủy văn Quốc tế lần thứ XXXVIII tại Krakow, Ba Lan - Giảng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
1. GROUNDWATER QUALITYSUSTAINABILITY1.1. Evaluation and management of groundwater -sustainable exploitation1.2. Groundwater vulnerability and quality standards1.3. Urban hydrogeology1.4. Groundwater quality and agriculture1.5. Groundwater quality and mining1.6. Groundwater monitoring1.7. Groundwater policy and legal aspects1.8. Economic tools to protect groundwater1.9. Sustainable management of groundwater1.10. Decision support tools for sustainablegroundwater management2. GROUNDWATER AND DEPENDENTECOSYSTEMS2.1. Global climate change and water budget2.2. Climate induced changes of land-use and theirimpacts on evolution of the EU GroundwaterDirective2.3. Interactions of surface and ground waters2.4. Water in extreme conditions (arid and polarregions)2.5. Wetland hydrology2.6. Groundwater in eco-hydrology2.7. Integrated groundwater management withdependent ecosystems3. AQUIFER MANAGEMENT3.1. Regional groundwater systems3.2. Trans-boundary aquifers3.3. Geophysical, geological and geochemicalmethods in groundwater exploration3.4. Environmental and artificial tracers inhydrogeology3.5. Social, ecological and economic implications4. MINERAL AND THERMAL WATER4.1. Geothermal resources4.2. Origin of mineral and thermal waters4.3. Hydrogeochemical characteristics of mineraland thermal waters4.4. Social, ecological and economic implications2875. DATA PROCESSING IN HYDROGEOLOGY5.1. Modelling as a tool of groundwater assessment5.2. Groundwater flow and solute transport modelling5.3. Groundwater mapping - approach and results6. GENERAL HYDROGEOLOGICALPROBLEMS6.1. Hard rocks as specific media - methods and results6.2. Hydrogeology of karst6.3. Groundwater contamination - monitoring, riskassessment and restoration6.4. Cost-effective measures to control and containgroundwater contamination6.5. Risk-based groundwater management(brownfields, industrial/postindustrial and urban areas)6.6. Coastal zone management6.7. Managing aquifer recharge6.8. Understanding and communication ongroundwater - education and public involvement